Summary of Research Progress on Friction Stir Welding of Dissimilar Metals - Zhang, Tingliang; Gao, Huaqiang; Xie, Baocheng (Recent Patents on Engineering, 2023)
Background: Friction stir welding technology is widely applied in the welding of dissimilar metal materials because of its high welding efficiency, low welding process cost, high welding joint strength and reliability, and green environmental protection. The research on the processing methods and working principle of friction stir welding of dissimilar metals is beneficial to improve the mechanical properties of the joint and reduce weld defects. Therefore, the development of reliable friction stir welding technologies for dissimilar metals joining has been paid increasing attention in recent years. Objective: The study aims to satisfy the processing of various dissimilar metals and improve the joint performance and weld defects. Friction stir welding has developed into bobbin tool friction stir welding and stationary shoulder friction stir welding. Methods: This paper retraces various current representative patents relative to friction stir welding, bobbin tool friction stir welding, and stationary shoulder friction stir welding. Results: Through the investigation of a large number of patents on friction stir welding, the main current existing problems, such as poor mechanical properties of the joints and defects in the welds, are summarized and analyzed. In addition, the development trend of friction stir welding in dissimilar metal welding is also discussed. Conclusion: The research on friction stir welding methods and devices is beneficial to improve the mechanical properties of welded joints and reduce weld defects. More correlative patents will be invented in the future.
Keywords: bobbin tool friction stir welding